Low prevalence of high blood pressure in pregnant women in Burkina Faso: a cross-sectional study - Franck Garanet; Sekou Samadoulougou; Adama Baguiya; Bruno Bonnechère; Tieba Millogo; Jean-Marie Degryse; Fati Kirakoya-Samadoulougou; Seni Kouanda (BMC, 2022)
Abstract Background High blood pressure (HBP) during pregnancy causes maternal and fetal mortality. Studies regarding its prevalence and associated factors in frontline level health care settings are scarce. We thus aimed to evaluate the prevalence of HBP and its associated factors among pregnant women at the first level of the health care system in Burkina Faso. Methods This cross-sectional study was conducted in six health facilities between December 2018 and March 2019. HBP was defined as systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg. Multivariable logistic regression analysis was performed to identify factors associated with HBP. Results A total of 1027 pregnant women were included. The overall prevalence of HBP was 1.4% (14/1027; 95% confidence interval [CI] 0.7-2.3), with 1.6% (7/590; 95% CI 0.8-3.3) in rural and 1.2% (7/437; 95% CI 0.6- 2.5) in semi-urban areas. The prevalence was 0.7% (3/440; 95% CI 0.2-2.1) among women in the first, 1.5% (7/452; 95% CI 0.7-3.2) in the second and 3% (4/135; 95% CI 1.1-7.7) in the third trimester. In the multivariable analysis, pregnancy trimester, maternal age, household income, occupation, parity, and residential area were not associated with HBP during pregnancy. Conclusion The prevalence of HBP among pregnant women at the first level of health system care is significantly lower compared to prevalence's from hospital studies. Public health surveillance, primary prevention activities, early screening, and treatment of HDP should be reinforced in all health facilities to reduce the burden of adverse pregnancy outcomes in Burkina Faso.